Pedagogical English Practice and Educational German Technology in the Federal State of Santander - Pérez Pinzón, Luis Rubén (Universidad Pedagógica y Tecnológica de Colombia, 2018)
European development models and economic initiatives of German businessmen influenced the educative and didactic innovations in the Federal State of Santander (1857-1886) that were adopted as the education system in the United States of Colombia. In this article, the causes of the substitution of the Lancasterian method by the Pestalozzi method, the educational contributions from educators such as Victoriano Paredes and Dámaso Zapata, as well as the effects of the German Pedagogical Mission are examined. Finally, the instructive role played by technological resources like didactic journals, the specialized books by pedagogues and the educational manuals for teachers in their classrooms according to the radical ideology are demonstrated.